A new species of porcelain crab, Petrolisthes tuerkayi n. sp. (Crustacea: Anomura: Porcellanidae), from the Persian Gulf - Naderloo, Reza; Apel, Michael (Zootaxa, 2014)
A new species of porcellanid crab, Petrolisthes tuerkayi n. sp., is described from the Persian Gulf. The new species is closely related to P. rufescens Heller, 1861, but is easily distinguishable by having three or four large spines distally on the posterior margin of the carpus of chelipeds, whereas the posterior margin of the cheliped merus in P. rufescens is unarmed.